Some geometric properties of a new sequence space - Karakaş, Murat; Cinar, Muhammed; Et, Mikail (My University, 2013)
In this paper, we introduce a new sequence space denoted by m (?, p, u, ?ru) and give some properties of this sequence space. Also, we examine Banach-Saks property of type p for this space. Finally, we find Gurarii's modulus of convexity and so show that the sequence space m(?, p, u, ?ru) is uniformly and strictly convex. © 2013 by Eudoxus Press, LLC, all rights reserved.
Keywords: Banach-saks property; Difference sequence; Gurarii's modulus of convexity; Strict convexity; Uniform convexity